Propaganda and international relations / Urban G. Whitaker, Jr - Whitaker, Urban G. Jr. (Estados Unidos de América: Howard Chandler Publisher, 1960)
The nature and role of propaganda in internacional relations, history and defenition of propaganda; propaganda agenies of the superpowers, propaganda activities of the superpowers, proposals for government acton on the psychological front, cessaion of nuclear testing a case study in international propaganda.
Contents, selected reading
327 W5749
Keywords: 1. INTERNATIONAL RELATIONS 2. PROPAGANDA-INTERNATIONAL RELATIONS 3. POLITICAL SCIENCE 4. SOCIOLOGY